Computation of Modified Möbius Indices of Some Oxide and Silicate Related Networks (Journal of Informatics and Mathematical Sciences, 2025)
Topological indices describes the topology of chemical graphs in terms of mathematical expressions to comprehend both physical and chemical features of the compounds involved. The scientific study of chemical graphs is a significant discipline in the applied mathematics to support the ideas evolved with respect to chemical graphs by means of different topological indices. The specific formulations of recently designated degree-based adapted Möbius indices have been determined in this piece through evaluating a number of oxide and silicate networks as well as their various variations.